A Highly Stretchable and Sensitive Strain Sensor Based on Dopamine Modified Electrospun SEBS Fibers and MWCNTs with Carboxylation. (9th June 2021) - Zhou, Bangze; Liu, Zhanxu; Li, Chenchen; Liu, Mengsi; Jiang, Liang; Zhou, Yanfen; Zhou, Feng‐Lei; Chen, Shaojuan; Jerrams, Stephen; Yu, Jianyong
Abstract: Wearable flexible electronic strain sensor devices have developed rapidly in recent years due to their potential capacity to detect human motion in various situations. However, it still remains still a big challenge to fabricate strain sensors with high sensitivity over a wide workable strain range. In order to meet this challenge, a new type of strain sensor based on elastomer/carbon nanotube composite fiber is reported in this work. Elastomer fibers are initially prepared via the electrospinning of styrene ethylene butene styrene block copolymer (SEBS). The resultant SEBS fibers are then functionalized by sequentially coating with dopamine (DA) coating and carboxyl group (‐COOH) grafted multi‐walled carbon nanotubes (MWCNTs) under vacuum filtration and ultrasonication. Scanning electron microscopy (SEM) and thermogravimetric analysis reveals that a large amount of MWCNTs is firmly bonded onto the SEBS fibers and evenly distributed. SEBS@PDA/MWCNTs composite fibers based strain sensors exhibit excellent performance, including a high gauge factor of 3717 and large workable strain range up to 530%. Furthermore, the developed sensors demonstrate excellent washing fastness and superior sensitivity in monitoring both small strains (e.g., pulse beats and vocal cord vibrations) and large strains (e.g., finger, elbow, and knee bending). Abstract : This work reports a new type of strain sensor based on multi‐walled carbon nanotubes functionalized styrene ethylene butene styrene fiber membrane prepared via electrospinning and vacuum filtration. It exhibits a high gauge factor of 3717 and a large workable strain range up to 530%. Furthermore, the developed sensor demonstrates excellent sensitivity in monitoring human motions.